2016
DOI: 10.11604/pamj.2016.25.114.8303
|View full text |Cite
|
Sign up to set email alerts
|

Ethical implications of HIV self-testing: the game is far from being over

Abstract: The use of combined Anti-Retroviral Therapy (cART) has been revolutionary in the history of the fight against HIV-AIDS, with remarkable reductions in HIV associated morbidity and mortality. Knowing one's HIV status early, not only increases chances of early initiation of effective, affordable and available treatment, but has lately been associated with an important potential to reduce disease transmission. A public health priority lately has been to lay emphasis on early and wide spread HIV screening. With man… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
5
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 9 publications
0
5
0
Order By: Relevance
“…ART initiation was lower in the HIVST arms compared to the standard-of-care arm, although it approximately doubled between the 1- and 4-month visits, from 25% to 50%. Both linkage to care and ART initiation increased rapidly in the HIVST arms, approaching the standard-of-care arm by 4 months, supporting the hypothesis that linkage to care and ART initiation take longer with HIVST, and mitigating some concern that individuals who self-test will not link to care [ 30 ]. By 4 months, ART initiation in the standard testing arm approached previously described estimates of ART coverage among FSWs in Zimbabwe [ 14 ] and exceeded a previous global estimate of 36% among FSWs in low- and middle-income countries [ 31 ].…”
Section: Discussionmentioning
confidence: 80%
“…ART initiation was lower in the HIVST arms compared to the standard-of-care arm, although it approximately doubled between the 1- and 4-month visits, from 25% to 50%. Both linkage to care and ART initiation increased rapidly in the HIVST arms, approaching the standard-of-care arm by 4 months, supporting the hypothesis that linkage to care and ART initiation take longer with HIVST, and mitigating some concern that individuals who self-test will not link to care [ 30 ]. By 4 months, ART initiation in the standard testing arm approached previously described estimates of ART coverage among FSWs in Zimbabwe [ 14 ] and exceeded a previous global estimate of 36% among FSWs in low- and middle-income countries [ 31 ].…”
Section: Discussionmentioning
confidence: 80%
“…A key concern with self‐testing is whether self‐testers would seek HIV treatment . This study demonstrated a noteworthy 100% linkage to HIV treatment; the national linkage rate is 31% .…”
Section: Discussionmentioning
confidence: 99%
“…The goal of increasing the number of people who get tested for HIV is to be able to get people under treatment and to ultimately have PLHIV with undetectable viral load. Ensuring linkage to care should then be a condition for selftesting to be effective, in addition to post-test counseling for behavioral change in the case of a negative HIV test (Bain et al, 2016). Linkage to care is limited in WCAR, with a weak health system and a lack of policies on HIVST.…”
Section: Fourth Challenge: Linkage To Hiv Prevention and Care Services/facilitiesmentioning
confidence: 99%